2022
DOI: 10.15557/pimr.2022.0031
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disorders in chronic kidney disease

Abstract: The increasing prevalence of chronic kidney disease gives rise to many diagnostic challenges in the daily care of this group of patients. This paper presents the most clinically significant endocrine disorders accompanying chronic kidney disease, their aetiology, diagnosis, clinical picture and treatment. Endocrine disorders may occur in patients with chronic kidney disease with greater or equal frequency as in the general population. The most important endocrine disorders include: low triiodothyronine syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A study by Gimenez-Perez et al found that isolated AITD was associated with a lower incidence of kidney disease, while the co-occurrence of other AID elevated the incidence of ischaemic heart disease (8) . Both hyperthyroidism and hypothyroidism in several complex processes can lead to pre-renal and renal kidney damage by affecting renal blood flow, glomerular filtration rate (GFR), and renal tubular function (23) . Prinz et al point to an increased risk of diabetic nephropathy in patients with T1DM and HT, although levothyroxine replacement therapy makes it possible to reverse this pathomechanism and demonstrates a nephroprotective effect (18) .…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 99%
“…A study by Gimenez-Perez et al found that isolated AITD was associated with a lower incidence of kidney disease, while the co-occurrence of other AID elevated the incidence of ischaemic heart disease (8) . Both hyperthyroidism and hypothyroidism in several complex processes can lead to pre-renal and renal kidney damage by affecting renal blood flow, glomerular filtration rate (GFR), and renal tubular function (23) . Prinz et al point to an increased risk of diabetic nephropathy in patients with T1DM and HT, although levothyroxine replacement therapy makes it possible to reverse this pathomechanism and demonstrates a nephroprotective effect (18) .…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 99%